Parenting, Academic Success, and Social-Emotional Satisfaction of Children - Baruwal, Himal (Bhairahawa Campus Journal, 2025)
The purpose of article on the relationship between teenage academic achievement and parenting. The various factors that influences children’s academic achievement and socioemotional expansion, with a focus on the role of parenting practices and involvement in education. This article aims to provide insight into how attitudes, parental behavior and support system impact children’s learning and outcomes, thereby informing policymakers, educator, politician, youth and parent themselves about effective strategies for promoting positive and reformist education for children who are the future nation builders. Researcher applied interview schedules and collected both qualitative and quantitative data. This research will be useful for parents and academician.